An all-weather Li/LiV2(PO4)3 primary battery with improved shelf-life based on the in situ modification of the cathode/electrolyte interface. Issue 33 (6th August 2020) - Ma, Di; Song, Zihan; Zhang, Hongzhang; Hussain, Arshad; Feng, Kai; Zhang, Huamin; Li, Xianfeng
Abstract : Herein, an all-weather Li/LiV2 (PO4 )3 primary battery with long shelf-life was developed by understanding the mechanism of self-discharge and modifying the cathode/electrolyte interface. Abstract : The development of primary batteries with high energy density, long shelf life, and stable discharge voltage is essential for civilization and military applications. Primary batteries with high power output and excellent low-temperature performance can further broaden their application. Herein, a Li/LiV2 (PO4 )3 primary battery was proposed and investigated for the first time. In order to improve the shelf life of the Li/LiV2 (PO4 )3 primary battery, the mechanism and corresponding inhibition strategy of self-discharge were studied in detail. It was found that the electrolyte composition is a key factor affecting the shelf life of Li/LiV2 (PO4 )3 primary batteries, where the corrosion of aluminum (Al) current collector triggered by the organic radical cations generated from electrochemical oxidation of the ethylene carbonate (EC) at high potential; and the detrimental reaction between LiV2 (PO4 )3 and electrolyte lead to the self-discharge of the Li/LiV2 (PO4 )3 primary battery. When the EC solvent was replaced by the propylene carbonate (PC) solvent, the corrosion of Al foil was alleviated. Moreover, the addition of lithium bis(oxalato)borate (LiBOB) to the electrolyte could improve the stability of cathode/electrolyte interface and enhance the shelf life of the Li/LiV2 (PO4 )3 primary battery. As a result, 100% capacity could be maintained after over one-month storage, 86% energy could be maintained at 50C, and 63% energy could be maintained at −40 °C at a current density of 0.1C. In addition, the Li/LiV2 (PO4 )3 primary battery showed great potential for all-weather applications.